Penguatan Pengelola Lahan Kelengkeng di Perkebunan Sentool melalui Teknologi Berbasis IoT - Maududie, Achmad; Swasono, Dwiretno Istiyadi; Adiwijaya, Nelly Oktavia (Institut Teknologi dan Sains Mandala, 2024)
Sentool Plantation is one of the plantations in Jember Regency that is currently promoting longan as one of its superior products. From the results of previous observations, two problems were found, namely workers having difficulty in monitoring the land and inefficient use of water resources. To overcome these problems, an appropriate technology for controlling irrigation and monitoring land conditions based on the Internet of Things (IoT) is prepared that can help Sentool plantation workers in managing the longan plantation area. The implementation of this activity is divided into three stages, namely: development of irrigation control system and monitoring of land conditions, system integration, and implementation and socialization to plantation employees as the use of the system. This activity has succeeded in realizing the intended system in the form of hardware and software to control the irrigation system and monitoring with four required indicators, namely soil moisture, air humidity, air temperature, wind speed, and rainfall measurements. At the socialization stage, the enthusiasm of the Sentool plantation employees can be seen from the liveliness in participating in the socialization stage of the use of the system to assist land management. Currently, the plantation employees also know how to operate the system so that they can reduce the constraints of the irrigation system and can see the condition of the longan fields through the application.